Prevalence and potential impact of human pegivirus-1 on HIV-1 disease progression among Indian PLHIV - Diviya Alex; Runal J Steve; Veena V Ramalingam; John P Demosthenes; Gopinathan Vijayalakshmi; Ben C Ghale; Priscilla Rupali; George M Varghese; Dolly Daniel; Grace Rebekah; Gnanadurai J Fletcher; Priya Abraham; et al. (Journal of Infection in Developing Countries)
Introduction: Human pegivirus-1 (HPgV-1) influences the pathogenesis and outcome of viral infections. We investigated the prevalence and impact of HPgV-1 due to the paucity of studies on Indian people living with HIV (PLHIV).